A Codon-Pair Bias Associated With Network Interactions in Influenza A, B, and C Genomes - Plant, Ewan P.; Ye, Zhiping (Frontiers in Genetics, 2021)
Codon deoptimization is used to attenuate viruses for vaccine development but the mechanism underlying attenuation is not well understood. Here we report a codon-pair bias present in the genomes of different types of influenza virus. Codons with fewer network interactions are more frequency paired together than other codon-pairs in influenza A, B and C genomes. A shared feature among three different influenza types suggests an evolutionary bias. Codon-pair preference can affect both speed of protein translation and RNA structure. This newly identified bias may provide insight into mechanisms of viral attenuation observed via genomic recoding.